2016
DOI: 10.1021/acsami.6b02842
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Li Diffusion Dynamics and Nanostructuring of H2Ti12O25 To Enhance Its Li Storage Performance

Abstract: Dodecatitanate H 2 Ti 12 O 25 crystal has a condensed layered structure and exhibits noteworthy Li storage performance that makes it an anode material with great potential for use in Li-ion batteries. However, an unknown Li diffusion mechanism and a sluggish level of Li dynamics through elongated diffusion paths inside this crystal has impeded any forward development in resolving its limited rate capability and cyclic stability. In this study, we investigated the Li diffusion dynamics inside the H 2 Ti 12 O 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…As observed in Figure a–c, the various crystal facets of H 2 Ti 12 O 25 in the [1 0 0], [0 1 0], and [0 0 1] directions correspond to different atom‐bonding models. It was reported that moving along the [0 1 0] direction ( c axis) may correspond to a low‐energy barrier pathway for Li + ‐ion diffusion . Hence, diffusion along the [0 1 0] direction of the (0 1 0) facet may present the lowest energy barrier pathway for Li + ‐ion diffusion.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As observed in Figure a–c, the various crystal facets of H 2 Ti 12 O 25 in the [1 0 0], [0 1 0], and [0 0 1] directions correspond to different atom‐bonding models. It was reported that moving along the [0 1 0] direction ( c axis) may correspond to a low‐energy barrier pathway for Li + ‐ion diffusion . Hence, diffusion along the [0 1 0] direction of the (0 1 0) facet may present the lowest energy barrier pathway for Li + ‐ion diffusion.…”
Section: Resultsmentioning
confidence: 99%
“…Such a result demonstrates the excellent cyclic stability of m‐H 2 Ti 12 O 25 , especially at an ultrahigh charging and discharging current density of 20C. Such outstanding high‐rate characteristics of the m‐H 2 Ti 12 O 25 nanorods is, to the best of our knowledge, much greater than those of currently reported H 2 Ti 12 O 25 listed in Table S2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations